Detection of forensic identification and intelligence SNP data from latent DNA using three commercial MPS panels. Issue 1 (December 2019) - Young, J.M.; Martin, B.; Kanokwongnuwut, P.; Linacre, A.
Abstract: Massively parallel sequencing (MPS) offers the ability to detect and analyse low quantity and quality DNA present on touched items. Here, we present MPS identity and intelligence SNP data generated from latent DNA using direct PCR and three different forensic panels: (1) the QIAGEN 140-SNP forensic identification multiplex (2) the 24 SNP HIrisplex System and (3) the 165 SNP Precision ID Ancestry Panel. The effect of individual and substrate type (wire, glass and zip-lock bag) on the recovery of SNPs and prediction accuracy was examined and compared across the three panels.